LINKAGES IN THE DEVELOPMENT AND DELIVERY OF AGRICULTURAL RESEARCH INFORMATION BY NIGERIAN RESEARCH INSTITUTES (1990)
A special communication system exists in each of the eighteen (18) National Agricultural Research Institutes which is responsible for linking the institutes and their researchers with public and private sector organization and people, including the States’ Extension Services and farmers. Consequently, the researcher considered it necessary to critically analyse these communication linkages in the development and delivery of agricultural information between the Research Institutes and the various target organizations. With the aid of the questionnaire technique, data collection was carried out in the eighteen (18) National Agricultural Research Institues in Nigeria. The chi-square (x2), the one-way analysis of variance (ANOVA), the Duncan's Multiple Range ANOVA and the Kruskal-Wallis tests were applied to determine the relationship between the variables. Personal observations were also used as complementary data to provide additional answers to the research questions. Six research questions related to the problem of study were examined. The results showed that National Agricultural Research Institutes maintain functional relationship with some relevant public and private sector organisations, in addition to the extension service, in the processes of developing and delivering agricultural information. The results also showed that effective communication linkages with the target organizations are associated with variables such as type of research institute, purpose of communication, frequency of contacts, communication methods, specific problem areas, choice of target organizations and the need for linkages. It was found out from the study that the frequency of contacts with the various target organizations is lower for problem formulation than it is for results dissemination. The study indicated that: i) the target organization influences the purpose of communication; ii) communication methods used by research institutes are significantly related to the purpose of communication; iii) type of research institute influences the communication methods used in problem formulation but not in results dissemination; iv) communication methods used by research institutes depend, to a great extent, on the target organization; v) with regards to problems formulation and results dissemination, there is an association between specific problem areas and the target organisations; vi) there is a significant difference in the ranking of communication methods used by Agricultural Research Institutes in contacting the various target organizations; and vii) Communication methods used by research institutes are determined by the specific problem areas. Findings showed that all the eighteen (18) National Agricultural Research Institutes affirmed the need for them to maintain effective communication linkages with other organization and people, and to enhance the linkages between them and the extension services.